Collaborative Strategies for Community Empowerment: A Narrative Study on Thematic Village Development in Malang, Indonesia - Mujibur Rahman Khairul Muluk; Asti Amelia Novita; Wishnu Mahendra Wiswayana (Journal of Contemporary Governance and Public Policy, 2025)
This study employs narrative analysis to examine collaborative initiatives supporting the development of thematic communities in Malang City, Indonesia. Drawing on the experiences of government officials, community members, and NGO representatives, the research highlights the importance of participatory governance, community engagement, and the unique features of thematic villages in advancing sustainable local development. Cases such as Kampung Sanan, known for tempeh production, and Kampung Heritage Kayutangan, valued for its cultural and historical significance, illustrate how local innovation and identity can empower communities and boost tourism. Thematic village development aligns with the Sustainable Development Goals (SDGs), particularly Goal 1 (No Poverty), by fostering inclusive economic opportunities. However, challenges such as limited stakeholder engagement, power imbalances, and the marginalisation of vulnerable groups may hinder progress towards Goal 5 (Gender Equality) and Goal 10 (Reduced Inequalities). Ecological sustainability is also central to the approach, especially regarding Goal 11 (Sustainable Cities and Communities) and Goal 13 (Climate Action). The findings suggest that effective coordination, strong political support, and inclusive participation are vital to improving quality of life and local income. This study offers practical insights and policy recommendations for strengthening collaborative frameworks that promote sustainable and inclusive thematic village development.